Review on Climate Change Adaptation and Mitigation Mechanisms in Ethiopia - Amenu, Bekele Tona; Amamo, Barena Adare; Borko, Teshome Tadewos (International Journal of Scientific Research in Civil Engineering, 2017)
Climate change is the burning issue of the current world because it is considered to be one of the most serious threats to sustainable development, with adverse impacts expected on the environment, human health, food security, economic activity, natural resources and physical infrastructure. Climate change, biodiversity and forest loss are issues inextricably interlinked and need to be addressed simultaneously. Climate is the fundamental factor that determines different stages of the organism life-cycle, such as plant germination and flowering. Causes for vulnerability of Ethiopia to climate variability and change include very high dependence on rain fed agriculture which is very sensitive to climate variability and change, under-development of water resources, low health service coverage, high population growth rate, low economic development level, low adaptive capacity, inadequate road infrastructure in drought prone areas, weak institutions, lack of awareness, etc. The objective of this paper is to examine the social, economic and environmental impacts of climate change based on their degree of existence and trends the impacts, to identify the adaptation strategies and mitigation measures and to find out the challenges to the adoption of those coping mechanisms. The effects of the changing climate are imposing impacts upon the social, economic and environmental conditions of the human beings by affecting their livelihoods causing poor living, housing, and health conditions, by reducing the number at the same time of the production of livestock. Traditional and contemporary coping mechanisms to climate variability and extreme in Ethiopia include changes in cropping and planting practices, reduction of consumption levels, collection of wild foods, use of inter-household transfers and loans, increased petty commodity production, temporary and permanent migration in search of employment, grain storage, sale of assets such as livestock and agricultural tools, mortgaging of land, credit from merchants and money lenders, use of early warning system, food appeal/aid, etc.
Keywords: Climate Change; Coping Mechanism; Impacts Of Climate Change